THE RELATIONSHIP OF ERECTILE DYSFUNCTION DRUGS USE WITH SEXUAL BEHAVIOUR AND SEXUALLY TRANSMITTED INFECTIONS AMONG MEN WHO HAVE SEX WITH MEN IN BELGRADE - Bjekic, Milan; Salemovic, Dubravka; Vlajinac, Hristina; Marinkovic, Jelena (HEALTH CARE, 2023)
Background/Aim: Erectile dysfunction (ED) drugs are increasingly being used for recreational purposes and improving sexual performance. Oral phosphodiesterase 5 inhibitors are the most popular type of ED drugs among men who have sex with men (MSM). The aim of this study was to assess the prevalence of ED drugs use among MSM in Belgrade and its association with their behaviour and sexually transmitted infections.Methods: A cross-sectional study was conducted at two public health care services in Belgrade and it covered 469 MSM. Data on demographic characteristics, sexual history, sexual behaviour, ED drugs and other recreational drugs use in the previous six months were collected from all participants by the use of a questionnaire.Results: Of all 469 respondents, 16.2% have been using ED drugs. According to the results of multivariate logistic regression analysis, ED drugs users, compared to non-users were older (Odds Ratio – OR=2.60, Confidence interval – 95%CI 2.77-3.84, (p
Keywords: drugs, erectile dysfunction, men who have sex with men, sexual behaviour, sexually transmitted infections